TELAAH FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI KOTA PADANG BERDASARKAN BERAT BADAN PER TINGGI BADAN MENGGUNAKAN METODE CART - Izzati Rahmi H.G (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
This study was conducted to determine factors that affect the nutritional status of children under 5 years of age in Padang City West Sumatra based on weight-for-height using Classification and Regression Tree (CART). The study was carried out in 4 districts in Padang City. A Total of 311 under 5 years of age children was examined. Children nutritional status are assess using weight-for-height Z score complied with WHO standard for children growth. Factors those were hypothesized to influence children nutritional status were gender, age, family income, maternal education level, number of children and score of maternal knowledge about nutrition. Data were analyzed using tree classification methods namely CART method. It was found that there were 3 variables that affect children nutritional status i.e age, family income and maternal knowledge about nutrition.